Implementation of The Iot System as The Condition Regulator of The Electrical Engineering Department's Laboratory Room - Setyawan, Indra; Suyono, Hadi; Nur Hasanah, Rini (Faculty of Engineering, Universitas Brawijaya, 2022)
Technological developments in the 4.0 era are currently growing rapidly, one of the advantages is that it makes it easier for users to control electronic equipment remotely. Only with a device, users can access all information through connectivity called the Internet of Think. The Internet of Things is a technological concept where all electronic equipment is interconnected with internet media so that it can be controlled or monitored from wherever the user needs it. The purpose of this research is to create a room condition control system based on the Internet of Think, where the device can be operated either automatically according to the schedule we set or manually. This system also has a monitoring system via a web server so that we can control and monitor the device without having to approach the device to turn it on or off. The device made in this study utilizes a temperature sensor and a smoke sensor as a sensor input medium to the controller. As an output, it utilizes a servo that is used to open and close the window so that the condition of the room can be controlled. To control the device remotely, the device is connected wirelessly by using wifi media which is one of the features of the nodemcu controller. The output of this research is the servo status on the window, fan, and air content displayed on the device and the web so that comfortable room conditions can be created according to the predetermined set point.